A review of adipose-derived mesenchymal stem cells‘ impacts and challenges: metabolic regulation, tumor modulation, immunomodulation, regenerative medicine and genetic engineering therapies - Wang, Lihong; Jiang, Xiaorui; Zhao, Fen; Duan, Ping; Li, Zhengguang; Luo, Yiqiao (Frontiers in Endocrinology, 2025)
Adipose-derived mesenchymal stem cells (ADSCs), multipotent stromal cells abundant in adipose tissue, exhibit remarkable plasticity in modulating systemic metabolism, inflammatory responses, and immune homeostasis. Their bidirectional interactions with the tumor microenvironment (TME) position them as both accomplices and antagonists in cancer progression, offering unique therapeutic opportunities. ADSCs also hold significant potential for clinical application in the fields of regenerative medicine, tissue engineering, and gene engineering. This review synthesizes the impacts and challenges of ADSCs involving metabolic regulation, tumor modulation, immunomodulation, regenerative medicine and genetic engineering therapies—while elucidating underlying molecular mechanisms and signaling pathways, clinical studies, applications and challenges.